1998
DOI: 10.1046/j.1471-4159.1998.70041712.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Activity Relationships of Conformationally Constrained Peptide Analogues of Loop 2 of Brain‐Derived Neurotrophic Factor

Abstract: Brain-derived neurotrophic factor (BDNF) promotes the survival of various neuronal populations and thus shows potential in the treatment of neurodegenerative disease. However, BDNF is not pharmacokinetically optimal for use as a therapeutic agent. As a step toward the development of low-molecular-weight BDNF-like drugs, we have designed a series of small, conformationally constrained peptides of various sizes using the threedimensional structure of BDNF derived by homology modeling as a template. When tested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 26 publications
1
35
0
Order By: Relevance
“…For example, replacement of the residues of loop 2 from NGF with the corresponding residues from loop 2 of BDNF gives a molecule able to bind to and activate TrkB (16). In support of this, we have shown that monomeric monocyclic peptides designed to mimic a single loop 2 of BDNF act as antagonists of BDNF-mediated neuronal survival in culture (17). The x-ray crystal structure of the complex of NGF with one of the Ig domains of TrkA shows that residues from loop 1 of NGF make direct contact with the receptor (18).…”
Section: Bdnfmentioning
confidence: 72%
See 2 more Smart Citations
“…For example, replacement of the residues of loop 2 from NGF with the corresponding residues from loop 2 of BDNF gives a molecule able to bind to and activate TrkB (16). In support of this, we have shown that monomeric monocyclic peptides designed to mimic a single loop 2 of BDNF act as antagonists of BDNF-mediated neuronal survival in culture (17). The x-ray crystal structure of the complex of NGF with one of the Ig domains of TrkA shows that residues from loop 1 of NGF make direct contact with the receptor (18).…”
Section: Bdnfmentioning
confidence: 72%
“…The three sequential p75 NTR -binding residues in loop 4 of BDNF (Lys 94 -Lys 95 -Arg 96 ) were isolated from a model of the three-dimensional structure of BDNF derived via homology modeling techniques (17,23). Using visual examination, a wide range of means of constraining this tripeptide were explored, from which a selection were built by adding appropriate amino acid(s) to the tripeptide and forming a single bond between the N and C termini.…”
Section: Molecular Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…TDP6 is a highly conformationally constrained tricyclic dimeric mimetic of the loop 2 region of BDNF that acts as a putative TrkB agonist (O'Leary and Hughes, 1998). We have previously shown that TDP6 is very potent in promoting sensory neuronal survival and that this is potentially mediated via TrkB signalling (O'Leary and Hughes, 2003).…”
Section: Tdp6 Activates Trkb Signalling In Primary Oligodendrocytes Cmentioning
confidence: 99%
“…The ability of synthetic peptides to promote neuronal survival was assessed in primary cultures of dorsal root ganglion (DRG) sensory neurons obtained from embryonic chicks using the method previously described by our laboratory, 7,9 which is based on the protocol first described by Barde and co-workers. 35 Peptides were examined in log 10 increments over the following ranges: Peptide 1: 1 Â 10 À10 to 1 Â 10 À5 M); peptides 2-6: 1 Â 10 À8 to 1 Â 10 À5 M; peptide 7: 1 Â 10 À8 to 1 Â 10 À5 M as well as from 1 Â 10 À10 to 1 Â 10 À5 M. Experiments were performed in triplicate, a total of three or four times.…”
Section: Sensory Neuron Survival Assaymentioning
confidence: 99%